Analysis of Public Street Lighting for Road Users Case Study: Cigasong Market, Majalengka - Rifatunnisa; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2025)
Majalengka is one of the cities that lacks lighting, significantly affecting community activities. In addition, public street lighting helps increase traffic comfort and safety, reduces crime rates, and improves people's quality of life. Lighting also impacts the economic sector, which is needed in some places, for example, in traditional markets. In these conventional markets, trading is not only done during the day or regular hours of human activity. Some traders and market consumers trade at night for convenience or because prices are lower than during the day. Because of this, market traders and consumers complain about the lack of lighting in the market area, which limits visibility, and sometimes criminality occurs. Accordingly, the purpose of this study is to examine the deficiency of street lighting in the Sindangkasih market area, Cigasong, an economic sector area. This study uses the perception variables of road users and market consumers to assess the lack of lighting at Sindangkasih Market, Jalan Raya Cigasong, Kab. Majalengka. Primary data came from questionnaires completed by 60 road users and market consumers surveyed. The parameters used were respondents perceived On a scale of 1 to 5, from not significant to very important and from not satisfied to very satisfied, rate the significance and level of satisfaction with the street lighting on this road. Critical performance analysis was used to process the data (IPA) technique. The results of this research are expected to provide solutions and changes for future spatial arrangements that lead to better regional development in terms of infrastructure and various other aspects, especially in public street lighting.